Pelatihan Kader Survailans Berbasis Masyarakat Sebagai Upaya Penguatan Puskesmas - Anggorodiputro, Raden Roro Ratuningrum; Hanipah, Sansan Nurul; Paryono, Jendi Ari (FKM UIN Sumatera Utara Medan, 2023)
AbstractCommunity-Based Surveillance is a Surveillance activity that uses information sourced from the community as a basis for decision-making in terms of planning, implementing, monitoring, evaluating programs and increasing awareness and responding to extraordinary events (KLB) quickly and precisely by policy holders. The aim of the SBM Cadres is to increase the role of community members in efforts to detect early COVID-19 and Non-Communicable Diseases so that cases are immediately handled by Health Workers. Training Methods with debriefing material through power point presentations on COVID-19 and Vaccination, Stunting, Non-Communicable Diseases and the Role of SBM Cadres. The result of this service is that there is an increase in the knowledge of SBM cadres after carrying out health education and there is strengthening cooperation for the puskesmas. The conclusion in this community service is the commitment of cadres in strengthening puskesmas related to COVID-19, Vaccination, Elderly and Non-Communicable Diseases